Deep‐blue light‐emitting polyfluorenes containing spiro[fluorene‐9, 9′‐thioxanthene‐S, S‐dioxide] isomers. Issue 14 (29th April 2017) - Peng, Feng; Xu, Jin; Zhang, Yuhao; He, Ruifeng; Yang, Wei; Cao, Yong
ABSTRACT: Blue light‐emitting polyfluorenes, PPF‐FSOs and PPF‐SOFs were synthesized via introducing spiro[fluorene‐9, 9′‐thioxanthene‐ S, S ‐dioxide] isomers (2, 7‐diyl and 2′, 7′‐diyl) (FSO/SOF) into the poly[9, 9‐bis(4‐(2‐ethylhexyloxy) phenyl)fluorene‐2, 7‐diyl] (PPF) backbone, respectively. With the increasing contents of FSO and SOF moieties, the absorption and PL spectra of PPF‐FSOs show slight red shift, while that of PPF‐SOFs exhibit blue shift, respectively. The HOMO and LUMO levels reduce gradually with increasing SOF unit in PPF‐SOFs. The polymers emit blue light peaked around 430–445 nm and show an excellent spectral stability with the variation in current densities. The distinctly narrowing EL spectra were observed with the incorporation of isomers in the polymers. The full width at half maximum reduced by 15 nm for PPF‐SOFs, resulting in a blue shift with the CIE coordinates from (0.16, 0.11) to (0.16, 0.08). With a device configuration of ITO/PEDOT:PSS/EML/CsF/Al, a maximum luminance efficiency (LEmax ) of 2.00 cd A −1, a maximum external quantum efficiency (EQEmax ) of 3.76% with the CIE coordinates of (0.16, 0.08) for PPF‐SOF15 and a LEmax of 1.68 cd A −1, a EQEmax of 2.38% with CIE (0.16, 0.12) for PPF‐FSO10 were obtained, respectively. The result reveals that spiro[fluorene‐9, 9′‐thioxanthene‐ S, S ‐dioxide] isomers are promising blocks for deep‐blue light‐emitting polymers. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 2332–2341 Abstract : PPF‐FSOs and PPF‐SOFs containing spiro[fluorene‐ 9, 9 ′‐thioxanthene‐ S, S ‐dioxide] isomers (2, 7‐diyl and 2′, 7′‐diyl) (FSO/SOF) emit blue light peaked around 430–445 nm with an excellent spectral stability. The distinctly narrowing emission was observed with the increasing content of isomers in the polymers. The nonconjugated SOF moiety in the polyfluorene backbone effectively disturbed the conjugation, restrained intramolecular charge transfer effect and kept a deep blue emission with Commission International de l Eclairge coordinate around (0.16, 0.08). A EQEmax of 3.76% was obtained from the single‐layer device based on PPF‐SOF15, which denoted a threefold enhancement compared with poly[9, 9‐bis(4‐(2‐ethylhexyloxy) phenyl)fluorene‐2, 7‐diyl]‐based device.